2019
DOI: 10.1186/s13011-019-0217-2
|View full text |Cite
|
Sign up to set email alerts
|

Current practices and perceived implementation barriers for working with alcohol prevention in occupational health services: the WIRUS OHS study

Abstract: Background Alcohol is associated with detrimental health and work performance outcomes, and one to three out of ten employees may benefit from interventions. The role of occupational health services (OHS) in alcohol prevention has received little attention in research. The primary aims of this study were to explore current practices of alcohol prevention targeting employees in occupational health settings, and examine whether and which perceived implementation barriers were associated with alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 59 publications
(68 reference statements)
0
23
0
Order By: Relevance
“…The present study used cross-sectional data collected between 2014 and 2018, and reported by employees from the private and public Norwegian workforce. Other results from the WIRUS project are published elsewhere [2631].…”
Section: Methodsmentioning
confidence: 99%
“…The present study used cross-sectional data collected between 2014 and 2018, and reported by employees from the private and public Norwegian workforce. Other results from the WIRUS project are published elsewhere [2631].…”
Section: Methodsmentioning
confidence: 99%
“…Data for the current study was obtained from the alcohol screening component of WIRUS project. More details and other results from the WIRUS can be found elsewhere [19][20][21][22][23][24].…”
Section: Design and Settingmentioning
confidence: 99%
“…Data for the current study was obtained from the alcohol screening component in the WIRUS project. More details and other results from the WIRUS project are published elsewhere (Aas et al, 2017; Nordaune et al, 2017; Thørrisen et al, 2018, 2019a,b; Skogen et al, 2019).…”
Section: Methodsmentioning
confidence: 99%